PARTIAL VERSUS TOTAL UROGENITAL MOBILIZATION IN UROGENITAL RECONSTRUCTION: A META-ANALYSIS - Putra, Prima Ciko Ade; Widia, Fina; Alam, Gampo; Wahyudi, Irfan; Rodjani, Arry (Indonesian Urological Association, 2020)
Objective: Urogenital sinus, cloacal malformation and congenital adrenal hyperplasia are some of the congenital anomalies which comprehensive management should be done to achieve better outcomes. Total Urogenital Mobilization (TUM) and Partial Urogenital Mobilization (PUM) are the most widely used in term of surgical management. However, many researches showed different outcomes of those procedures. This meta-analysis aims to compare the outcome of TUM and PUM in urogenital reconstruction. Material & Methods: Studies were collected from five different search engines (PubMed, EBSCO, ProQuest, Science Direct, Google Scholar) with keyword as mentioned in the methods section of this paper. All full text articles were included. Critical appraisal for each study was done using the Oxford Center of Evidence Based Medicine Worksheet for therapy. Data were analyzed by Cochrane's Review Manager 5.3 for charts and plots builder. Results: Three studies were found with 81 participants divided into PUM or TUM group. All studies were analyzed by using the Mantel-Haenszel test to produce Forest plot. Overall, urinary incontinence event was more common found in patient who underwent TUM compare with PUM (OR 8.21; 95%CI: 1.1-61.11; p=0.04). Conclusion: PUM has a better urinary outcome in comparison with TUM. Further study with a better study design, follow-up and standardized evaluation is needed to achieve a better understanding on urogenital reconstruction and management.